LKPD Digital Berbasis Soal HOTS pada Pembelajaran Tematik untuk Mengembangkan Critical Thinking Skill - Laila Fatmawati; Berfi Lestari (UM Purwokerto Press, 2022)
This study aims to develop digital LKPD based on Higher Order Thinking Skill (HOTS) questions that support the critical thinking skills of fifth grade students, especially on environmental change material and analyze the quality of digital LKPD based on Higher Order Thinking Skill (HOTS) in fifth grade thematic learning in schools. base. This type of research is research and development with reference to the ADDIE model. Data were obtained through expert assessment sheets, interviews, and observations. Higher Order Thinking Skill (HOTS) Question-Based Digital LKPD teaching materials were declared feasible by validators of material, media, learning, and language experts. The results of the material validator assessment obtained an average value of 3.41 categorized as very good, the media validator assessment obtained an average value of 3.33 categorized as very good, the learning validator assessment obtained an average value of 3.54 categorized as very good, and the language validator assessment obtaining an average score of 3.50 is categorized as very good. Based on the results of the validator's assessment, it is stated that the Digital LKPD teaching materials based on Higher Order Thinking Skills (HOTS) meet the quality for use in the learning process.